Explosion protection electrical apparatus and systems for chemical plants, oil and gas industry, coal mining - Groh, Heinrich (Amsterdam ; Boston : Elsevier/Butterworth Heinemann, 2004)
This book makes Hazardous or Electrical Area Classification simple. In plants processing flammable materials, every effort is made to avoid the escape of such materials and in addition, stringent measures are taken to exclude sources of ignition. A complex array of standards surround this topic which has lead to an overly conservative approach being taken. This type of approach means that much more expensive electrical apparatus than is necessary is installed. To avoid this unnecessary expenditure, Dr Groh clearly explains the relevant standards, so that accurate assessment of the risks associated with hazardous areas is possible. He also identifies possible ignition sources and methods of designing apparatus which do not cause sparks thereby maintaining safety. * Covers must-have information regarding IEC/CENELEC standards in electrical or hazardous area classification * Provides a clear overview of a complex area.
Basic principles of explosion protection. -- The classification of hazardous areas. -- Standards for electrical apparatus and systems in Zone 1. -- Grouping and classification of explosion protected electrical apparatus. -- Marking and selection of explosion protected apparatus. -- The different types of protection -- constructional requirements. -- Analyzers and analyzer rooms. -- Testing explosion protected electrical equipment. -- Financial considerations -- selecting explosion protected electrical equipment. -- Inspection, maintenance and repair of explosion protected equipment. -- Explosion protected apparatus for Zone 0 and Zone 2. -- Cable protection in coal mines and other areas hazardous due to combustibles. -- Bibliography. -- Index.
Includes bibliographical references and index.
Keywords: Mine gases; Firedamp; Explosions -- Safety measures; Explosionproof electric apparatus and appliances; Chemical plants -- Safety measures; Electronic books